The role of uncertainty avoidance in foreign investment bias - Burcu Erdogan (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
In this paper, I explore the determinants of foreign bias in international portfolio investment focusing on a behavioral explanation. Specifically, I investigate whether investors having a stronger uncertainty aversion perceive a foreign country to be more unfamiliar than those with less such aversion. I exploit systematic differences in uncertainty avoidance across countries in my analysis using Hofstede's (1980, 2001) findings for this purpose. I show that less familiarity with the foreign markets discourages investors from investing abroad and that this effect is more pronounced the more uncertainty averse the investor, even after controlling for different sources of risk. I provide compelling evidence that uncertainty avoidance helps to explain foreign bias and that it has an amplifying effect on unfamiliarity and should be accounted for when modeling portfolio choices.
Keywords: F30; G11; G15; Z13; 330; foreign bias; home bias; international portfolio investment; uncertainty avoidance